2008
DOI: 10.1016/j.syapm.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and identification of Pantoea species associated with plants, humans and the natural environment based on multilocus sequence analysis (MLSA)

Abstract: Species belonging to the genus of Pantoea are commonly isolated from plants, humans and the natural environment. The species of the genus are phenotypically closely related, making rapid identification of Pantoea strains to the species level difficult. Multilocus sequence analysis (MLSA) was evaluated as a means for rapid classification and identification of Pantoea strains. Four housekeeping genes, gyrB, rpoB, atpD and infB, were sequenced for strains assigned to the genus. Included in the study were (1) refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
262
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(291 citation statements)
references
References 43 publications
8
262
2
1
Order By: Relevance
“…Confirming the uncertainty of P. agglomerans identification, only 20 of the 53 strains received from culture collections as P. agglomerans, Pantoea spp., or E. agglomerans clustered with type strain LMG 1286 T according to gyrB sequencing. Seven strains previously assigned to P. agglomerans were found to fit in the MLSA groups of Pantoea recently described as new species (i.e., C9-1 as P. vagans; EM13cb and SC-1 as P. anthophila; LMG 5343 and ATCC 29001 as P. brenneri; and EM17cb as P. conspicua), or to belong to a novel subspecies of P. agglomerans (Eh252) (4,6,7,45). The remaining strains were reassigned to other Pantoea species or Enterobacteriaceae, although precise identification was not possible in all cases.…”
Section: Vol 76 2010mentioning
confidence: 97%
See 2 more Smart Citations
“…Confirming the uncertainty of P. agglomerans identification, only 20 of the 53 strains received from culture collections as P. agglomerans, Pantoea spp., or E. agglomerans clustered with type strain LMG 1286 T according to gyrB sequencing. Seven strains previously assigned to P. agglomerans were found to fit in the MLSA groups of Pantoea recently described as new species (i.e., C9-1 as P. vagans; EM13cb and SC-1 as P. anthophila; LMG 5343 and ATCC 29001 as P. brenneri; and EM17cb as P. conspicua), or to belong to a novel subspecies of P. agglomerans (Eh252) (4,6,7,45). The remaining strains were reassigned to other Pantoea species or Enterobacteriaceae, although precise identification was not possible in all cases.…”
Section: Vol 76 2010mentioning
confidence: 97%
“…Accurate identification is complicated by the unsettled taxonomy of the "P. agglomerans-E. herbicola-E. agglomerans" complex (45). Recent analyses based on gyrB sequencing, multilocus sequence analysis (MLSA) (4), and fluorescent amplified fragment length polymorphisms (fAFLP) (45) indicate that strains belonging to Enterobacter or Erwinia archived in culture collections are often erroneously assigned to P. agglomerans and are likely also misidentified in clinical diagnostics. False classifications of environmental P. agglomerans strains as related Pantoea species, including human-or plant-pathogenic P. ananatis, are also common (45).…”
Section: P Agglomerans Is a Composite Taxon Conglomerating Formermentioning
confidence: 99%
See 1 more Smart Citation
“…Multilocus sequence analysis (MLSA) based on gyrB, rpoB, atpD and infB sequences was used in these studies as a supporting phylogenetic technique, since these genes were previously shown to be useful phylogenetic markers for Pantoea (Brady et al, 2008). In that study, strains from DNA HG II, IV and V (referred to as MLSA groups E, F, H and I) and Pectobacterium cypripedii were suggested to be members of the genus Pantoea.…”
mentioning
confidence: 99%
“…of Brady et al (2008). Purification and sequencing (Sanger method) of PCR products were carried out by the Shenggong Company in Shanghai, China.…”
mentioning
confidence: 99%